EVALUASI PROGRAM PENDIDIKAN DAN PELATIHAN PIMPINAN ESELON III DI LINGKUNGAN KEMENTRIAN AGAMA RI - SYAUKANI SYAUKANI (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2011)
This is an evaluation study on the training program for the echelon III leader at the Ministry of Religious Affairs. This study utilizes the four levels of Kirkpatrick’s evaluation modelreaction, learning, behavior, and results. There are 30 respondents in this study; All of them are the echelon III leaders at the Ministry of Religious Affairs all over Indonesia. The finding of the study shows that the 23rd training program conducted by the center for education and training of the Ministry of Religious Affairs can be categorized well performed, since 85% of the projected program can be utilized, the substances of the training can be understood and applied at the participants’ work environment. However, this study also finds some parts of the training program that ought to be reformed in order to get a better result or outcomes in the future training program. The data informs us that the use of the outsider tutors is still important in order to get a broader knowledge for those who participate in the training and the facilities to support the training should be improved.